Pemanfaatan Layanan Perpustakaan Digital dalam Meningkatkan Minat Baca Mahasiswa Universitas Padjadjaran - Batubara, Rosa Mardiani (Pustabiblia: Journal of Library and Information Science, 2023)
Reading activities cannot be separated and are very essential with students because reading is the most important activity in students’ lives and activities. Unfortunately, currently, student’s reading interest looks very minimal. The student’s low interest for reading can be seen from the number of visits in each campus library. However, one of the factors causing the low interest in reading is advances in information technology. With advances in information technology, students prefer to find information quickly rather than precise information. In general, this study aims to see and describe the influence of digital libraries on reading interest of students in the library and informa- tion science study program at Padjadjaran University. From this research, it is known that the factors causing the declining quality of reading interest are physiological, intellectual, environmental and psychological factors. With the existence of a digital library, it is expected to increase students’ reading interest. This research uses a litera- ture study method from related references and data collection is carried out using a qualitative approach. The level of interest in reading a nation greatly determines the quality of human resources, while the quality of human resources greatly determines the development of a nation.